Analisis Pembelajaran Berbasis Loose Parts terhadap Perkembangan Kognitif Anak Usia Dini di KB Pelangi Harapan - Dewi Retnowati; Itsnaini Muslimati Alwi (ARZUSIN, 2026)
Although loose parts-based learning has increasingly received attention in early childhood education, studies that specifically examine its implementation in relation to the cognitive development of children within particular early childhood education institutions remain relevant to be developed. This study aims to analyze the implementation of loose parts-based learning on the cognitive development of early childhood children at KB Pelangi Harapan. This study employed a descriptive qualitative method with data collection techniques consisting of observation, interviews, and documentation, with the research subjects including teachers and students at KB Pelangi Harapan. The findings showed that loose parts-based learning was able to stimulate children’s cognitive development, particularly in recognizing the shapes and sizes of objects, grouping objects, counting simple quantities of objects, and arranging various objects into certain forms according to the children’s imagination. In addition, play activities using loose parts also increased children’s activeness, creativity, and ability to solve simple problems. The teacher’s role as a facilitator in providing learning materials and giving guidance during play activities also became an important factor in supporting successful learning. The conclusion of this study confirms that loose parts-based learning is an effective strategy for supporting the cognitive development of early childhood children and strengthening play-based learning practices in early childhood education institutions.